Структура систем ортопроекторів, пов’язаних зі зліченними деревами Кокстера - Кириченко, А.А.; Самойленко, Ю.С.; Тимошкевич, Л.М. (Український математичний журнал, 2014)
Исследуются представления алгебр типа Темперли-Либа, которые порождены ортопроекторами, связанными со счетными деревьями Кокстера. Доказана теорема, описывающая структуру таких систем ортопроекторов, и приведены примеры. The paper is devoted to the investigation of representations of Temperley–Lieb-type algebras generated by orthogonal projections connected with countable Coxeter trees. The theorem on the structure of these systems of orthogonal projections is proved. Some examples are presented.